Is the East Catching Up?: The Development of Public Investment in East and West Germany - Dieter Vesper (Weekly Report, 2005)
Expanding and modernizing the infrastructure is generally regarded as essential for East Germany to catch up with the west. The question concerning the quality and quantity of the infrastructure in East Germany played a central role in the negotiations for both Solidarity Pact I and Solidarity Pact II. However, while only very sparse information and estimates were available on the level of state fixed assets for the negotiations in spring 1993, the decisions for Solidarity Pact II in 2001 could rely on a broader data base. Estimates by DIW Berlin on state fixed assets in East and West Germany played an important part. They in turn were based on an estimated development in public investment for the years 1998 to 2004. A comparison of this with the actual development in east and west Germany shows considerable discrepancies between the forecast and the actual figures.
Keywords: 330